Incidence of post-operative pulmonary complications following emergency laparotomy in tertiary care centre in Vindhya region of Madhya Pradesh, India - Gangwal, Mohit; Singh, Brijesh (International Surgery Journal, 2018)
Background: Pulmonary complications after abdominal surgery, including pneumonia, atelectasis and respiratory failure, are significant cause for patient suffering, prolonged hospital stays and increased mortality rate. There are well documented cases of atelectasis, pneumonia, aspiration pneumonitis, Acute respiratory distress syndrome, pleural effusion, empyema, tracheobronchitis etc. Present study aims at studying the incidence of pulmonary complications following emergency laparotomy. Methods: A total of 271 patients who got admitted through SOPD, casualty or transferred from other departments and underwent emergency laparotomy during the period of study were included in the study irrespective of the age and sex. Post operatively patients were regularly monitored and with advent of clinical and investigative findings post-operative pulmonary complications were recorded and incidence was calculated. Results: The mean age of the patients in present study was 36.1 and standard deviation of 15. Out of 271 patients, 219 were males 52 were females. Most common etiology of peritonitis was Peptic perforation (35.4%) followed by ileal perforation (23.6%). Incidence of post-operative pulmonary complications in present study was 30.2%. Conclusions: Post-operative pulmonary complications continue to be a significant morbidity following emergency laparotomies. Preoperative risk factors include smoking history, pre-existing lung disease and cardiac dysfunction. Emergency nature of the procedure, long duration operation and midline incision are the other factors that can increase the risk of PPC. Early identification and aggressive treatment goes a long way to tide over the progress to a life-threatening state.